Evaluation of the effect of the neurotoxin MPTP and the antiparkinsonian drug hemantane on the DNA integrity in the brain structures of C57BL/6 mice - E. A. Anisina; A. K. Zhanataev; A. V. Nepoklonov; S. O. Kotelnikova; E. A. Valdman (LLC "Publisher OKI", 2022)
Hemantane (N-adamant-2-yl-hexamethylenimine hydrochloride) is an antiparkinsonian drug with a multicomponent mechanism of action, including a modulating effect on the activity of dopamine and serotonergic mediator systems, a selective inhibitory effect on MAO-B, properties of a low-affinity non-competitive channel blocker of glutamate NMDA receptors, has moderate antiradical and anti-inflammatory activity. The aim of this study was to assess the effect of the neurotoxin MPTP, which is used for modeling of parkinsonian syndrome, and the hemantane on the DNA integrity in the striatum and frontal cortex of the brain of C57BL/6 mice by the DNA comet assay - gel electrophoresis of DNA single cells. Results. In the first experiment, hemantane was administered once a day for 5 days before the MPTP (20 mg/kg, i.p.), then together with MPTP once a day for 5 days. In the second experiment hemantane 10 mg/kg was injected preliminarily for 4 days and 40 minutes before MPTP 30 mg/kg. The obtained results confirm the absence of an effect on DNA of hemantane at a therapeutic dose of 10 mg / kg. In the experimental schemes used, we did not reveal the expected increase in the level of DNA damage under the influence of MPTP, and, accordingly, we were not able to assess the protective effect of hemantane.